Pendampingan Dan Dukungan Motivasi Bagi Guru Dalam Upaya Meningkatkan Kwalitas Pembelajaran Melalui Power Point Di Sdn Kadilanggu 1 Kecamatan Baki Kabupaten Sukoharjo - Sri Wening; Maria Atik Sunarti Ekowati; Kristyana Dananti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
. Teacher competence is one of the capital in carrying out teaching duties, based on the competence that teachers have, it can create interesting and fun learning conditions. Power point media is one of the media in the learning process that needs to be mastered by teachers in carrying out learning in the digital era. But not all teachers have the knowledge and skills to understand and use power point as a technology medium in the learning process. Awareness of the need for teachers for knowledge and skills in using power points requires stimulus from schools and other institutions in an effort to provide mentoring and motivational support for teachers to develop self-actualization. Through mentoring and motivational support activities, teachers have skills and even become more skilled in choosing and functioning power points according to the subject matter they teach, so that teachers are motivated to improve the performance of carrying out an effective and efficient learning process